ELT Research Papers as Authentic Materials in Teaching Research-Based Article Writing: A Case in Indonesian Context - Ghufron, M. Ali (Journal of ELT, Linguistics, and Literature, 2017)
There are strong shreds of evidence that the choice of instructional materials has large effects on students’ achievement. This study was to assess the efficacy of using ELT research papers as authentic materials in teaching research-based article writing. This study was aimed at revealing whether or not there is a significant difference in students’ writing skill in terms of ELT research paper writing between the students who were taught by using ELT research papers as authentic materials and those who were taught by using textbook materials provided by the faculty. This study belongs to a quasi-experimental study with an experimental and control group pretest-posttest design. The population of this study was 75 students from the fourth semester of English Education Study Program of IKIP PGRI Bojonegoro, East Java, Indonesia. The sample was selected through cluster random sampling and consisted of 50 students that were divided into two groups. The instrument used to collect the data was a writing test. Consequently, normality and homogeneity of the data were tested. A t-test was used to compare the mean of the two groups. The hypothesis was designed and tested at 0.05 level of significance. The results revealed that there is a significant difference in students’ academic writing skill between the students who were taught by using the ELT research papers as authentic materials and those who were taught by using textbook materials. The t-test revealed that t-value is higher than t-table (6.07>2.01). Therefore it is concluded that the authentic instructional materials could significantly improve students’ academic writing skill.